Uslub Muqabalah dalam Al-Qur’an - Ummul Aiman; Masnaria Dewi Rahmah Siregar (TAFSE: Journal of Qur'anic Studies, 2017)
The Qur'an as a miracle for the Prophet SAW is unique and special, especially in terms of language. The beauty of the Qur'an will not be felt meaningfully without paying attention to the uslub used in it. One form of the beauty of the Qur'an in terms of meaning is al-muqabalah, which is to mention two or more words, then bring out the opposite of that meaning in sequence. On the one hand, the Qur'an has a language uslub that is different from other literature, but on the other hand, many people cannot absorb the beauty of the Qur'an in terms of meaning due to the difficulty of understanding Arabic rules that require explanation. This discussion was studied using the maudhu'i method, in the form of library research with descriptive data analysis. Research shows that in the Qur'an there are as many as 66 verses containing uslub muqabalah in different forms and many are mentioned in short verses. Comparison between the blessings and punishment of Allah is 36 verses, relating to the comparison of Allah's power in 8 verses, comparisons regarding the nature of believers and disbelievers in as many as 16 verses, and comparisons between commands and prohibitions in 8 verses. Uslub Muqabalah is one of the elements in Badi' Science which can be used as a tool to reveal beauty and become a uniqueness and privilege for the Qur'an. Al-Qur’an sebagai mukjizat bagi Nabi Saw memiliki keunikan dan keistimewaan khususnya dari segi bahasa. Indahnya al-Qur’an tidak akan dirasakan secara makna tanpa memperhatikan uslub yang digunakan di dalamnya. Salah satu bentuk keindahan al-Qur’an dari segi makna adalah al-muqabalah, yaitu menyebutkan dua kata atau lebih, lalu mendatangkan lawan dari makna tersebut secara berurutan. Di satu sisi, al-Qur’an mempunyai uslub bahasa yang berbeda dari sastra lain, akan tetapi di sisi lain banyak orang yang tidak dapat menyerap keindahan al-Qur’an dalam segi makna dikarenakan sulitnya memahami kaidah Bahasa Arab yang membutuhkan kepada penjelasan. Pembahasan ini dikaji dengan menggunakan metode maudhu’i, berupa riset kepustakaan (library research) dengan analisis data deskriptif. Penelitian menunjukkan bahwa dalam al-Qur’an terdapat sebanyak 66 ayat yang mengandung uslub muqabalah dengan bentuk yang berbeda-beda dan banyak disebutkan dalam ayat-ayat pendek. Perbandingan terkait antara nikmat dan azab Allah sebanyak 36 ayat, terkait perbandingan kekuasaan Allah 8 ayat, perbandingan terkait sifat orang-orang beriman dan orang kafir sebanyak 16 ayat, serta perbandingan antara perintah dan larangan 8 ayat. Uslub Muqabalah ini menjadi salah satu unsur dalam Ilmu Badi’ yang bisa dijadikan sebagai alat untuk menguak keindahan dan menjadi suatu keunikan dan keistimewaan bagi al-Qur’an.